TP53 and KRAS2 mutations in plasma DNA of healthy subjects and subsequent cancer occurrence: a prospective study. - Gormally, E; Vineis, P; Matullo, G; Veglia, F; Caboux, E; Le Roux, E; Peluso, M; Garte, S; Guarrera, S; Munnia, A; Airoldi, L; Autrup, H; et al. (2006)
In cancer patients, plasma often contains mutant DNA released by cancer cells. We have assessed the significance of plasma DNA mutations for subsequent cancer development in healthy subjects in a large longitudinal prospective study. The European Prospective Investigation into Cancer and Nutrition study was analyzed with a nested case-control design. Cases were nonsmokers or ex-smokers for >10 years and newly diagnosed with lung, bladder, or upper aerodigestive tract cancers or leukemia accrued after a median follow-up of 6.3 years. Controls were matched 2:1 for follow-up, age, sex, area of recruitment, and smoking status. KRAS2 mutations were detected by mutant-enriched PCR and sequencing (n = 1,098). TP53 mutations were detected by denaturing high-performance liquid chromatography, temporal temperature gradient electrophoresis, and sequencing (n = 550). KRAS2 or TP53 mutations were detected in 13 of 1,098 (1.2%) and 20 of 550 (3.6%) subjects, respectively, 16 of whom developed cancer on average after 18.3 months of follow-up. Among 137 subjects who developed bladder cancer, 5 had KRAS2 mutations [odds ratio (OR), 4.25; 95% confidence interval (95% CI), 1.27-14.15] and 7 had TP53 mutations (OR, 1.81; 95% CI, 0.66-4.97). There was a nonsignificant trend for association between TP53 mutations and bulky adducts in lymphocyte DNA (OR, 2.78; 95% CI, 0.64-12.17). This is the first report of TP53 or KRAS2 mutations in the plasma of healthy subjects in a prospective study, suggesting that KRAS2 mutation is detectable ahead of bladder cancer diagnosis. TP53 mutation may be associated with environmental exposures. These observations have implications for monitoring early steps of carcinogenesis.